Variations of the hero's journey in contemporary British, French and Australian picture books about the Great War - Kerby, Martin C., 1967- author. aut Link Link Link
1 online resource (160 pages)
Keywords: "This book is grounded in the belief that every nation had its own 'Great War', and that children's picture books are an important barometer of each country's national approach. To explore the depiction of the Great War in Australian, British, and French modern children's picture books, where this historical event is reimagined in different ways as a futile conflict, a painful victory, and as part of one country's founding mythology, this book uses the concept of the hero's journey as underlying framework. It claims that this monomythic pattern, as developed by Joseph Campbell and modified by Christopher Vogler, not only informs all picture books selected for this project but can also be used to highlight the extent to which modern children's picture book authors and illustrators conform to their respective nation's cultural memory. It further maintains that the specific historical context of the Great War in these children's picture books can be used to identify a variant of the hero's journey: the 'ordinary soldier's journey.' This analysis of children's picture books about the Great War through the lens of Campbell's hero's journey will be of interest to both students and researchers in the fields of children's literature, literary theory, history, cultural studies and education"-- Provided by publisher.